AL-QUR'AN'S SOLUTION IN THE QUARTER LIFE CRISIS PHASE TO ANXIETY (THEMATIC STUDY OF THE QUR'AN) - Ahmad Muhajir; Sadzid Tulic (Universitas Muhammadiyah Surakarta, 2022)
Human life is not without problems. When problems arise, humans tend to feel anxiety, stress, or even other illnesses that often result in confusion about what is the right solution to solve the problem. even though Allah SWT, in the Al-Qur'an has included many verses that provide solutions for all kinds of anxiety. One example of life anxiety is the quarter life crisis or a quarter century crisis. who feel worried about the future, have no clear direction, confused and distraught about the uncertainty. Usually this anxiety includes relationships, romantic relationships, careers, and social life. Based on this phenomenon mentioned, the author tries to further examine the Qur'an's solutions to the quarter life crisis phase. The method used to analyze the Al-Qur'an's solution to future anxiety uses thematic study of the Qur'an or commonly called maudhu'i. namely finding and collecting verses that contain anxiety and verses that provide solutions to anxiety in the Qur'an. The result of the research is that anxiety is not specifically discussed in the Qur'an, but reflects a broad implied value including its meaning. 1. Khauf, namely the state of the heart, there is no peace about something in the future 2.diiq namely the narrowness of the soul, triggered by doubts originating in the heart, 3.Halu’a namely the nature of complaining, and 4.huzn that is sad. Then the solutions in the Qur'an to avoid anxiety include: Striving hard to look at the future, Continuously trying to follow Allah's instructions, Istiqomah in goodness, Sincere, Reaching for the future with faith, piety and good deeds.